'The history of Ireland he knew before he went to school': The Irish Tom Raworth. Issue 1 (May 2016) - Cummins, James
Abstract : In an interview in 1971 Tom Raworth states 'I don't really see any reason for a term like "English poet"' and throughout his career Raworth has resisted such simple national classifications. His work is often discussed in relation to the strong relationship he fostered with American poets and poetics. Raworth, for many, exemplifies the transatlantic conversation that flourished during the 1960s onward. He was influenced by numerous schools of American poetry and would in turn act as an influence to many American writers. As Ted Berrigan states 'he's as good as we are, & rude a thing as it is to say, we don't expect that, from English poets today, (I wonder is he better?)'. However, considering Raworth's mother was Irish and that since 1990 Raworth himself has travelled under an Irish passport this simple duality of British / American does not go far enough in exploring Raworth's complex national poetic identity. Using a combination of contextual and biographical information alongside close readings of a number of collected and uncollected poems this essay explores the influence Ireland, its culture, religion and history, has had on Raworth's upbringing, his sense of national identity and his poetry.